Discontinuous Mayer control problem under state-constraints - Plaskacz, Sławomir; Quincampoix, Marc (Topological Methods in Nonlinear Analysis, 2000)
This paper deals with Mayer’s problem for control systems with state constraints and, possibly, discontinuous terminal cost. The main result of this paper consists in the characterization of the value function as the unique solution to an Hamilton-Jacobi equation. The above characterization extends results already obtained in the case of regular cost functions and under some controlability assumptions on the boundary of the set of constraints.